Health monitoring of cavitation erosion on airframe fuel pumps - Verhulst, Tedja (Cranfield University, 2023)
Aircraft maintenance is a critical aspect of operations that can lead to substantial financial savings if improved. The fuel pump is a vital component of the entire aircraft, ensuring fuel delivery to the engine. Cavitation is common in these pumps, leading to erosion and reducing the pump's remaining useful life. Therefore, the main objective of this work is to develop a viable health monitoring method to diagnose cavitation erosion, where few solutions exist. Initially, a literature review is conducted to identify knowledge gaps and opportunities for technology transfer related to current Health Monitoring (HM) technologies for airborne pumps. Four sensing methods, pressure, flow, current, and temperature sensing, are shortlisted based on their past applications and suitability for an aircraft fuel system installation. A hybrid health monitoring scheme consists of a Computational Fluid Dynamics (CFD) simulation, a model running on Simscape, and an experimental test rig. Live experiments are conducted to validate the simulation methods, enabling the testing of scenarios on a wide range of boundary conditions. The simulations demonstrate strong alignment with the experimental data and successfully distinguish the different levels of erosion. Three out of the four tested sensing methods are sensitive enough to distinguish the different levels of erosion, but each method has its advantages and limitations. Temperature sensing is not useful for health monitoring as the ambient environment strongly influences its results. Despite the success of the developed health monitoring schemes, there is a need for further research and development into more sophisticated health monitoring algorithms before the technologies can be widely implemented on aircraft.
Judt, David - Associate Supervisor
Keywords: Health Monitoring; Diagnostics; Airframe Fuel Pump; Airframe Fuel System; Computational Fluid Dynamics; Cavitation; Cavitation Erosion